Development and validation of a questionnaire to measure COVID-19 vaccine hesitancy within the Romanian industrial laborers - Turcu-Stiolica, Adina; Boicea, Ancuta Ramona; Nechita, Florina; Surugiu, Roxana; Dumitra, Gheorghe Gindrovel; Oancea, Carmen Nicoleta; Pîrlog, Mihail Cristian (Frontiers in public health, 2025)
The identification and quantification of sources of vaccine hesitancy among industrial workers in Romania have become crucial for developing effective strategies to facilitate the vaccination process. Our study included employees, both with and without comorbidities, who work in industrial companies. The goal was to develop a scale to assess COVID-19 vaccine hesitancy in Romania. This proposed scale has been designated as the Romanian COVID-19 Vaccine Hesitancy (RO-CVH) scale. The survey encompassed both the demographic characteristics of the respondents and questions related to their perceptions of COVID-19 vaccination. A three-stage process was used to develop the RO-CVH which includes (1) item generation; (2) item-refinement (pilot testing, exploratory factor analysis); and (3) scale validation. The fifteen items loaded onto three factors using exploratory factor analysis, explaining 63% of the total variance. The three factors were labelled as “Confidence in information regarding the COVID-19 vaccine,” “Safety and efficacy of the COVID-19 vaccine,” and “COVID-19 vaccination as a means of controlling the population.” The content validity of the scale was established, and it will be utilized to comprehend the behavior of industrial workers in Romania during similar future outbreaks, particularly regarding the acceptance of mitigatory vaccines. Based on the insights from this scale, future interventions could be designed to reduce vaccine hesitancy.